(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2007)
The wet granulation process still finds large applicability close to the modern pharmaceutical industry for the production of tablets, because it eliminates some of the main attributed problems of the direct compression: the segregation tendency and the low flow properties of the powders during the process. The present work evaluates and it compares through micromeritical studies and statistical analysis the flow characteristics of granulates destined to the development of tablets of hydrochlorothiazide 50 mg. Three binders were tested (paste of starch and the aqueous dispersions, prepared to cold, of pregelatinized starch and povidone). It was still evaluated the compatibility between the drug and the employed excipients, through termoanalytical studies (DSC), and the influence of the extra granular addition of the "superdisintegrant" crospovidone in the values of dissolution efficiency (%DE) of the obtained tablets. The obtained granulates presented good flow and compressibility properties, characterized by: values of compressibility index between 5 and 15; Hausner ratio less than 1,25 and angle of repose between 30 and 35º. The crospovidone addition did not increase the values of %ED of the developed formulations, in the experimental conditions employed, although it has reduced, in way a low significance, the disintegration times of the formulations.